2021
DOI: 10.1080/13696998.2021.1965388
|View full text |Cite
|
Sign up to set email alerts
|

Cost of hemophilia A in Turkey: an economic disease burden analysis

Abstract: Objective: Hemophilia A is the second most common bleeding disorder causing patients to have lifelong follow-up and treatment. Despite being a rare disease, hemophilia A has a high economic burden on individuals and the public. The purpose of this study was to estimate the total disease cost of hemophilia A in Turkey.Materials and Methods: Data used in this analysis were collected through literature review, including studies conducted in Turkey by December 2018. A disease burden analysis was performed by model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
(37 reference statements)
2
8
0
1
Order By: Relevance
“…The HERO 20 study, conducted in developed and developing countries such as China and Algeria, which could be more comparable with our study, stated that 63% of parents had problems with employment, causing an economic impact.A study estimated that nonformal caregivers in Turkey accompanied 55% of patients with hemophilia. 18 This rate is even higher during childhood, which can be a possible explanation for the unemployment of 1 parent of children with hemophilia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HERO 20 study, conducted in developed and developing countries such as China and Algeria, which could be more comparable with our study, stated that 63% of parents had problems with employment, causing an economic impact.A study estimated that nonformal caregivers in Turkey accompanied 55% of patients with hemophilia. 18 This rate is even higher during childhood, which can be a possible explanation for the unemployment of 1 parent of children with hemophilia.…”
Section: Discussionmentioning
confidence: 99%
“…The mean number of working days missed for a patient’s caregiver due to hemophilia A-related medical issues was 43.7 days/year, which was less than a recent study from Turkey that reported missed working days as 98.4 days/year. 18 In a study comparing caregivers’ employment in the UK, Sweden, and Canada, the percentage of caregivers of children with hemophilia who worked full time was less than that of caregivers of healthy children. 19 In a study conducted in European HTCs, including the Ege University HTC from Turkey, using the HEMOCAB questionnaire, most caregivers worked full time (39.2%) or part-time (35%).…”
Section: Discussionmentioning
confidence: 99%
“…RD patients and their families are therefore at higher risk of experiencing poor quality of life, increased mental health issues, more social isolation, and poor work-life balance [ 14 , 69 , 76 , 80 ]. Notably, the impact RDs have on the lives of patients and their caregivers is further exacerbated by the lack or limited reimbursement of orphan drugs and the consequent burden of out-of-pocket expenses on RDs households [ 69 , 81 , 82 , 83 ]. While the next section will include a more detailed account of the social and psychological impact of RDs on patients and their families, it is important to highlight the need for a more comprehensive body of RD-related policies that can respond to the multidimensional needs of support and care.…”
Section: Current Situation and Key Challenges Related To Rdsmentioning
confidence: 99%
“… Elaborated by authors based on overviewed literature [ 7 , 12 , 14 , 56 , 58 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. …”
Section: Current Situation and Key Challenges Related To Rdsmentioning
confidence: 99%
“…According to these numbers, rare diseases must affect more than 6 million individuals in Türkiye. Although rare diseases present heterogeneous clinical and genetic features, many of the social and economic obstacles are similar worldwide ( 7 9 ). Most of the patients suffer from misdiagnosis, or they even remain undiagnosed for years ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%